Comparison of the effects of different core exercise on muscle activity and thickness in healthy young adults - Ko, Mingyun; Song, Changho (Physical therapy rehabilitation science, 2018)
Objective: This study aimed to compare the effects of core exercise methods on muscle activation and muscle thickness in healthy young adults and to propose effective core exercise methods. Design: Three-group pretest-posttest design. Methods: A total of 30 healthy young adults (14 males, 16 females) voluntarily participated in the study. Subjects were randomized to the prone plank exercise (n=10), reverse plank exercise (n=10), or bridge exercise (n=10) groups. Muscle activity and thickness of the rectus abdominis (RA), multifidus (MF), external oblique (EO), and internal oblique (IO) muscles were measured using surface electromyography and ultrasound. Subjects from each group participated in the exercises five times a week, with five 20-second sets during week 1. The set time was increased by 10 seconds per week. Results: Muscle activity and thickness in the prone plank, reverse plank, and bridge exercise group were statistically significant different for RA, MF, EO, and IO changes over time, and interaction between time and groups were also significantly different (p<0.05). We analyzed statistically significant differences between groups using a one-way analysis of variance for each period. A significant difference was observed after 4 weeks of exercise (p<0.05). Conclusions: The results suggest that the prone plank exercise is a beneficial method for enhancing muscle activation and thickness of the RA, EO, and IO compared to the reverse plank and bridge exercises. On the other hand, the reverse plank and bridge exercises are effective methods for enhancing the MF compared to the prone plank exercise. KCI Citation Count: 1